Current immunosuppressive treatment and self-reported lifetime stroke history among United States adults: A cross-sectional study - Muhammad Saad Ansari; Fiza Nisar; Ufaq Reyaz; Mahnoor Fatima; Umair Ahmad Khan; Baseerullah Hadi; Muhammad Talha Khalid (PLoS ONE, 2026)
Current immunosuppressive treatment is used for autoimmune, inflammatory, malignant, transplant-related, and other chronic conditions that may carry elevated cerebrovascular burden. Nationally representative evidence on current immunosuppressive treatment status and self-reported lifetime stroke history remains limited. This cross-sectional study used pooled 2023–2024 National Health Interview Survey Adult Sample data. The analytic sample included adults aged 18 years or older with valid survey weights and complete data on exposure, outcome, and selected covariates. The exposure was current self-reported use of medications that weaken the immune system. The outcome was self-reported lifetime stroke history. Survey-weighted logistic regression estimated odds ratios and 95% confidence intervals, accounting for National Health Interview Survey stratification, clustering, and adjusted sampling weights. The final analytic sample included 60,026 adults, representing approximately 250 million United States adults. The weighted prevalence of current immunosuppressive treatment was 4.6%. Stroke history was more common among adults receiving immunosuppressive treatment than among those not receiving treatment (6.0% versus 2.8%). In unadjusted analysis, immunosuppressive treatment was associated with higher odds of stroke history (odds ratio 2.24, 95% confidence interval 1.86–2.70, p < 0.001). After full adjustment for age, sex, race/ethnicity, hypertension, diabetes, smoking status, coronary heart disease, and income-to-poverty category, the association persisted (adjusted odds ratio 1.71, 95% confidence interval 1.40–2.08, p < 0.001). Current immunosuppressive treatment status, likely reflecting both medication exposure and underlying disease burden, was associated with higher odds of self-reported lifetime stroke history among United States adults. Because of the cross-sectional design, broad exposure definition, self-reported outcome, and potential confounding by indication, these findings should be interpreted as an association rather than evidence of causation.